Numerical study of integrated solar photovoltaic–thermal module with a refrigeration system for air-conditioning and hot water production under the tropical climate conditions of Singapore - Dubey, Swapnil (2020)
Thermal systems of buildings in the tropics are highly energy intensive. In this study, a novel integrated solar photovoltaic–thermal–refrigeration (PVTR) system used to produce hot water and air-conditioning in the tropical climate conditions of Singapore was analyzed. A dynamic simulation model was formulated for the analysis. Mathematical models were developed for the PV sandwich attached with a solar flat plate collector and for the main components of the refrigeration system. Thorough investigation of the electrical and thermal performances of the system were conducted through the analysis of coefficient of performance (COP), cooling capacity, water temperature and heat capacity in water heater, photovoltaic (PV) module temperature and PV efficiency. The results show that attractive electrical and thermal performance can be achieved with a maximum annual cooling COP of 9.8 and a heating COP of 11.3. The PV efficiency and power saving were 14% and 53%, respectively. The annual cooling, heating and PV energy produced were 9.7, 15.6 and 1.6MWh, respectively. The financial payback period of the system was 3.2 years and greenhouse gas (GHG) emission reduction annually was 12.6 tons of CO2 equivalents (tCO2e).